MODERATE ISLAM IN LITERARY TEXTS BY K. H. MUSTOFA BISRI AND ITS RELEVANCE AS TEACHING MATERIALS AT SMAN 4 JEMBER - Shidiq Ardhianta (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2022)
Radical Islamic teachings penetrated the world of education. This was also experienced at SMAN 4 Jember. Prevention efforts involving teachers are very important, including Indonesian language teachers. Indonesian language teachers can play a role through literary learning. The research focuses on two things, namely (1) what moderate Islam is taught by K. H. Mustofa Bisri's literature through his literary works? (2) How can K. H. Mustofa Bisri's teachings on moderate Islam be integrated into teaching materials at SMA 4 Jember? The literary analysis stage begins with reading, recording, and content analysis. The validity of the research data was tested through validity and reliability tests. The validity test used is semantic validity, while the reliability test uses intrarater reliability and interrater reliability. The results of this study are as follows. There are several poems and short stories of K. H. Mustofa Bisri which specifically contain moderate Islamic education. This moderation partly rejects the extreme left, as in the short story